L’accueil des exilés à Berlin dans le roman Gehen, ging, gegangen (2015, Je vais, tu vas, ils vont, 2022) de Jenny Erpenbeck - Birte Gnaegy (Tr@jectoires)
In the novel Gehen, ging, gegangen (2015, Go, Went, Gone, 2017), Jenny Erpenbeck refers to the migration movement that shook Europe in 2015. By questioning the arrival of displaced persons in Berlin, the author is part of the revival of literary realism, which is characterized by the implementation of social criticism in the novel. This article examines the question of how the narrator portrays the plurality and also the divergence of different standpoints, which are expressed in a fictional society – with particular attention to narratological strategies. It also shows how the inequality and powerlessness of displaced persons in Germany are represented in a literary form.